Ultrafine structure of the hydroxyapatite amorphous phase in noninfectious phosphate renal calculi - Zelenková, Markéta; Sohnel, Otakar; Grases, Felix (Urology, 2012)
OBJECTIVE: We aimed to establish detailed morphology of the structureless amorphous hydroxyapatite (HAP) phase to improve our understanding of the formation mechanism of these concretions. Noninfectious phosphate renal calculi composed mainly of HAP consist of inorganic material in the form of spherules, in a seemingly structureless and amorphous phase and organic matter. METHODS: Several cross-sections of a fraction of phosphate renal stone composed solely of the amorphous HAP phase were examined with atomic force microscope. Both 2- and 3-dimensional images of their structure and nanoscale elastic modulus maps were obtained. RESULTS: The amorphous hap phase consists of 2 distinctly different morphologic forms of hydroxyapatite: separate and/or intergrown columnar crystals, and spherical agglomerates with diameters in the range 150-300 nm consisting of spherulites approximately 10 nm in diameter. The columnar crystals are irregularly disseminated in the stone interior, which is porous because of cavities with depths in excess of 100 nm. Organic matter is almost evenly distributed throughout the stone interior. CONCLUSION: Based on the observed calculus structure, the following mechanism of formation of the noninfectious phosphate calculi is suggested: Spherulites formed via the perikinetic aggregation of Posner's clusters present in urine supersaturated with respect to hydroxyapatite aggregate into spherical agglomerates that, after reaching a certain size, are retained in cavities with poor urodynamics, gradually settle, and become incorporated into developing concretion. The columnar crystals are probably nucleated on the detritus of organic origin embedded in the hydroxyapatite structureless phase.
Keywords: imunohistochemie; Kidney Calculi; Durapatite; Immunohistochemistry; Calcium Phosphates; lidé; ledvinové kameny; hydroxyapatit; fosforečnany vápenaté; Humans